The Perspectives of Organizational Power: A General Overview - Benny, Cornelia J (EDUCARE, 2009)
ABSTRACT: Power is a phenomenon appearing in the personal, interpersonal and structural behavior. Within the personal behavior, power is a need that has to be realized to get satisfaction. Accordingly, the power that is inherent in an organization is of dynamic character and may be regarded as a driving force to internalize its values so as to enable the organization to increase its adaptability to changes, and its productivity as well, which in their turn will boost its work satisfaction and efficiency. Based on the above statement, we may conclude that power means the ability or force that causes other people to do (or act) according to the desire of the power holder. In short it may be said that the process of building functional power will contribute (highly) to the organizational effectiveness. This paper tries to elaborate, in general overview, the power process in an organization (behavior, structure and process) that has the potential to interfere with the organizations success as a whole, a uniting factor will be much needed. Stated differently, the power process should be viewed as an effort to internalize those values that could make the organization to have the ability to changes, to be more productive, to upgrade the job satisfaction and efficiency. In short it may be said that the functional power process could well contribute to the effectiveness of the organization.KEY WORDS: power, organization, management, leadership, and effectiveness and successful in the organization.About the Author: Dr. Cornelia J. Benny is a Lecturer at the Postgraduate Program of UNINUS (Islamic University of Nusantara) in Bandung, West Java, Indonesia. For academic purposes, she can be contacted at: Jalan Cipedes Tengah No.208 Bandung, West Java, Indonesia. Tlp. +6222-2009452.How to cite this article? Benny, Cornelia J. (2009). âThe Perspectives of Organizational Power: A General Overviewâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.195-206. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (November 5, 2008); Revised (January 5, 2009); and Published (February 17, 2009).